A New Concept of Water Use Efficiency: A Case Study for Irrigation Schemes in Büyük Menderes Basin (Badan Pengembang Konservasi UNNES, 2022)
Classical water use efficiency concepts are appropriate tools for irrigation design and irrigation management, However, it is not sufficiently suitable for water allocation and transfer policies. The classical concept of efficiency is shown by the formula Ec = Uci/(1-LR) VD. This equation is based on crop water consumption Uci, leaching water requirement LR, and irrigation water diverted to the system VD. Classical water use efficiency concepts do not take into account the amount of flows returning from irrigation, such as re-entering the water source, deep seepage and irrigation runoffs. Therefore, efficiency improvement studies based on classical water use efficiency calculations do not result in real water savings. In order to overcome the limitations of classical water use efficiency, a new concept called efficient water use efficiency (Ee) in decision making for water resources is proposed. Ee is expressed as Uci/Ue, the Ue, representing the efficient use of water consists of the difference between effective inflow and effective outflow. Effective water use efficiency takes into account the quantity and quality of water distributed in a basin and returning to the water source when the inflow for each usage cycle is estimated. In this study, the efficiency of irrigation water used during the 2019 irrigation season in irrigation schemes of Nazilli, Akçay, Aydın and Söke located in the Büyük Menderes basin and connected to each other in terms of water resources was compared and calculated according to the classical project, developed classical and effective water use efficiency methods. In the analyzed basin irrigation schemes, classical efficiency was between 43-61%, developed classical efficiency 47-67% and effective efficiency 67-86%.